Efektifitas Pelaksanaan Wirid Remaja Sebagai Lokus Pembinaan Akhlak dalam Implementasi Instruksi Walikota Padang Nomor 451.286 Tahun 2012 di Kecamatan Koto Tangah - Irwandi Irwandi; Ahmad Lahmi; Syaflin Halim (Jurnal Kajian dan Pengembangan Umat, 2020)
Wirid youth activities, ramadhan pesentren and dawn education is one of the icons of religious activities in Padang City which was instructed by the Mayor with the Instruction of the Mayor of Padang No. 451.286 year 2012, This activity is carried out as a forum to instill the values of aqidah or morality, as well as as a platform to improve the reading ability of qur'an for teenagers in Padang City, especially those students of junior high school / MTs, but nevertheless not all mosques and mushalas in Tangah Yan City Sub-District carry out this activity. The implementation of Youth Wirid at Masjid and Mushala in Koto Tangah District of Padang city has generally been carried out in accordance with Padang Mayor's Instruction Number 451.286 year 2012. In terms of the effectiveness of Padang Mayor's Instruction No. 451.286 of 2012 in encouraging the Implementation of Juvenile Wirid in Mosques and Mushala in Koto Tangah District of Padang City, it was found that not all mosques or mushallas held carry out this instruction. The supporting factor of youth wirid activities in Mosques and Mushala in Koto Tangah Koto Padang sub-district is instruction from the mayor, caretaker or pincer wirid as well as the facilities and infrastructure owned by the mosque or mushala. Then the Inhibitor Factor consists of Internal and extrenal. The impact of Wirid Remaja and its Relevance to Moral Development in Mosques and Mushala in Koto Tangah Sub-District of Padang City, obtained results that the activities of this youth wirid has had a positive influence on the morality of teenage wirid participants, both morally on God, on others as well as on the environment.